Investors’ Attentiveness towards Mutual Funds in Nepal (Prithvi Academic Journal, 2020)
The growing enthusiasm for mutual funds among the investment choice is an anxiety in the Nepali capital market. The paper aims to find out the investors’ eagerness towards mutual funds in Nepal. This investigation is descriptive and based on a structured questionnaire survey of 125 (out of 140) respondents from the broker office in Chitwan District. The stratified sampling method was used, based on four strata (Businessperson, university lecturer, university student, institutional and local investor) of the respondents’ socio-demographic, adequate knowledge, and factors determination areas. The paper has three major discoveries. First, Nepali investors were dominated by male gender like as in other countries, and university students were excited in the capital market for investment that most common only in Nepal. Second, investors were investing in mutual funds without sufficient knowledge although most investors were aware of political instability. Lastly, investing in common stock rather than mutual funds, followed by the players who made the mutual fund more effective were the most prioritized factors and awareness to invest in mutual funds was the least factor while investing by an investor. Moreover, the correlation among all variables was positively significant. This paper is valuable to the government bodies, academicians, concern companies, and investors, which help them to know more about mutual funds. This study concludes differently from previous studies that individuals prefer to invest in the capital market rather than a bank deposit, which is probably the new appearance in Nepal.